Never forget the construction of collective memory of human rights violations during Martial Law through digital memorialization on Facebook - Del Rosario, Joelle Nadine G.; Rodrigazo, Je-Ann T.
This thesis examines the audience's viewing experiences in superhero media that depict themes of trauma. Specifically, it explores how audiences who have lost a loved one make meaning in the representation of loss and grief in the superhero series WandaVision. Previous studies on superhero media have shown the genre has the potential to provide personal value as well to critically reflect cultural and social issues. Thus, the main objective of the research is to understand the significance of superhero genre in representing trauma according to audiences who relate to such depictions. For its methodology, the study used non-probability purposive sampling to identify a sample of 10 participants who were fans of the series and have undergone loss in their lives, and then conducted semi-structured interviews to gather their readings of the series. For its analysis, the study mainly utilized Schroder's model of reception (2000) with trauma theory as a lens to identify recurring themes that indicate how audiences signify and respond to the series as a trauma-related text. Findings from the audience's readings show the series portrayed the complex and affective process of grieving which in turn enabled audiences who have lost a loved one to make sense and work through their experiences.